Beyond the sixties scoop: reclaiming indigenous identity, reconnection to place, and reframing understandings of being indigenous - Wright Cardinal, Sarah (2017)
This study used life experience methods to gather the narratives of seven adult Indigenous transracial adoptees who have reclaimed their Indigenous identities after experiencing closed adoption during the late 1950s through to the early 1980s. Participants had been members of Aboriginal (First Nations, Metis, Inuit) communities at birth but were then raised outside their Indigenous nations in non-Indigenous families. Through analysis of their stories, I identified four themes that marked their trajectories to reclamation: Imposed fracture (prior to reclamation); Little anchors (beginning healing); Coming home (on being whole); Our sacred bundle (reconciling imposed fracture). Their stories of reconnecting to their Indigeneity, decolonizing and healing illustrate their shifts from hegemonic discourse spaces that characterized their lived experiences as “other” to spirit-based discourses that center Indigenous knowledge systems as valid, life affirming, and life changing. This dissertation contributes to the debate on state sanctioned removal of children and the impacts of loss of Indigenous identity in Canadian society. My findings indicate that cultural and spiritual teachings and practices, as well as, the knowledge of colonization and its impacts on Indigenous families, communities, and nations, all contributed to adoptees’ healing and ability to move forward in their lives. Key recommendations include: further exploration of the concept of cultural genocide in relation to settler-colonial relations in Canada; further examination of the intersection of counter-narratives, resistance discourse, and colonial violence; increased investigation of the connections between Indigenous knowledge systems, living spirit-based teachings and educative aspects of community wellness; and more research examining education beyond formal schooling, including the formative effects upon Indigenous youth of social values, public policy, and legal frameworks. Graduate